2019
DOI: 10.7717/peerj.5965
|View full text |Cite
|
Sign up to set email alerts
|

Designing online species identification tools for biological recording: the impact on data quality and citizen science learning

Abstract: In recent years, the number and scale of environmental citizen science programmes that involve lay people in scientific research have increased rapidly. Many of these initiatives are concerned with the recording and identification of species, processes which are increasingly mediated through digital interfaces. Here, we address the growing need to understand the particular role of digital identification tools, both in generating scientific data and in supporting learning by lay people engaged in citizen scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…We expected identification ability to improve over time, as a result of verification feedback and learner experience [8,30,32,43]. We found that the accuracy of bumblebee identifications varied throughout the year in both projects, but did not show an improvement across months, probably because different bumblebee species emerge and are active at different times.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We expected identification ability to improve over time, as a result of verification feedback and learner experience [8,30,32,43]. We found that the accuracy of bumblebee identifications varied throughout the year in both projects, but did not show an improvement across months, probably because different bumblebee species emerge and are active at different times.…”
Section: Discussionmentioning
confidence: 93%
“…Recorders are encouraged to use the BeeWatch website resources, including a simple binomial key, to identify their bumblebee. All records are verified/corrected by experts at the University of Aberdeen or BBCT and automated feedback is provided to the recorder [3032].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment by Thornton et al strongly suggests that training and providing classifiers with detailed visual aids improves image classification, echoing results from Kosmala et al () and Sharma, Colucci‐Gray, Siddharthan, Comont, and Wal (). We still do predict that inexperienced and untrained undergraduate students would have poorer agreement compared to the experts used in our study if both groups examined the same images.…”
mentioning
confidence: 87%
“…Citizen scientist #2 processed 7,483 images, had 86.7% (4703 / 5422) accuracy identifying animal species, and 90.4% (6764 / 7483) accuracy in identifying the presence of an animal and then the correct species. Variability in human accuracy is an area that is starting to be examined more fully (Sharma et al 2019) in an attempt to improve accuracy for citizen science projects. For example, is the difference in accuracy a reflection of time taken when reviewing images or expertise?…”
Section: Camera Trap Image Processing: Engaging the Communitymentioning
confidence: 99%